Solidaritas Janda: Pemberdayaan Perempuan di PJJI Armalah Yogyakarta - Rohinah Rohinah; Nisfi Anisah (Sunan Kalijaga State Islamic University & The Asia Foundation, 2020)
Status Janda dapat menyebabkan subordinasi dan marginalisasi. Hal ini Nampak jelas pada perempuan yang sering mengalami pengucilan sosial dan perampasan ekonomi. Janda bukan hanya nasib kurang beruntung, miskin, dan orangtua tunggal akan tetapi sikap didiskriminasi adalah pemicu dari hilangnya hak ekspresi. Status janda juga menjadi sasaran kecurigaan dan tuduhan kejahatan moral. Paper ini bertujuan mengetahui spirit pendirian komunitas persaudaraan Janda-Janda Indonesia (PJJI) Armalah Yogyakarta serta program kegiatan dan program pendampingan atau advokasi. Hal tersebut mengeksplorasi kemungkinan agensi perempuan dan destigmatisasi dalam mobilisasi jejaring sosial pada penekanan nilai kehormatan sosial sebagai seorang ibu. Paper menunjukkan tata cara kerja PJJI Armalah yang fokus pada Janda dalam hak keadilan yang berlandaskan spirit cinta kasih dan persamaan kesejahteraan dalam nilai Pancasila. Hal ini mendorong para janda dalam sikap berani dan mandiri dalam kebenaran.[A widow condition talks the subordination and marginalization on Social frame. The Woman in status is especially evident in seeing the experience of social exclusion and economic deprivation. Widows are not only unlucky, poor, and single parents, but the attitude of being discriminated against is the trigger for the loss of the right to expression. The status of the widow was also putting to suspicion and allegations of moral crimes. This paper aims to find out the spirit of the establishment of the organization's human rights on persaudaraan Janda-Janda Indonesia (PJJI) Armalah Yogyakarta. It is as well as activities in advocacy programs. It explores the possibility of female agency and destigmatization in the social framework for the Social honor value as women and mothers. The paper shows the work procedures of PJJI Armalah which focuses on widows in the right of justice based on the spirit of love and equality. It puts welfare in the values of Pancasila. The idea encourages widows to be courageous and independent in righteousness.]